Musik dan Identitas: Analisis Konstruksi Identitas Sosial dalam Album “Menari dengan Bayangan” Karya Hindia - Muhammad Chamdan Husein; Sumekar Tanjung (Jurnal Mahasiswa Komunikasi Cantrik, 2022)
This study will focus on the meaning of personal identity for an album entitled Menari dengan Bayangan (Dancing with Shadows), created by a musician named Daniel Baskara Putra or the stage name Hindia. In the album, which contains 12 songs, Baskara gives implied messages about his identity in the songs on the album that his listeners will listen to. This study uses the semiotic analysis method of Ferdinand de Saussure, which focuses on the signifier and the signified aspects in interpreting each song lyric created by Baskara.